Propuesta de mejora del proceso de envasado de cerveza en la línea 1 en una empresa cervecera - Leyva Barzola, Jhon Marco (2019)
This research work develops the experimental use of total productive maintenance (TPM), in the beer packaging area of Backus and Johnston SAA, to eliminate waste and increase the productivity of the area in question. The investigation begins by mentioning the main theoretical concepts of total productive maintenance (TPM) from the steps to follow for its implementation, the four pillars of the development of this program, the advantages of implementing this work methodology, and some success stories after the its implantation After this description, the diagnosis of the current situation will be made, identifying problems such as mainly in the non-compliance of production, the lack of preventive and predictive maintenance and the little or no knowledge of the personnel in the equipment and machinery with which it works. To this end, different proposals for improvement are developed that will reduce the different problems that occur in terms of production compliance, which to date is generating economic losses. Likewise, for each particular problem, the proposals will be developed, such as the need to implement a preventive maintenance management system, autonomous maintenance work, training and training of employees on operational issues. At each point proposed, mention is made of the savings and benefits of making improvements. After having developed the implementation proposal, the benefits of this TPM implementation are presented. Having the production increase the plan to produce from 472129 to 478566 boxes, the production plan being 518494 boxes of beer per shift increasing with an efficiency of 92.28%. In addition, it improves the downtime of the machine stops, according to the results to the observed test of the machines an average availability of 85.39% and increase 86.85%, therefore, increase to 1.46%.